2014
DOI: 10.1007/s10815-014-0386-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes from mature oocytes derived from preovulatory and antral follicles: reflections on follicle physiology and oocyte competence

Abstract: Purpose The aim of this retrospective study was to compare the competence of oocytes obtained from preovulatory and antral follicles. Methods Mature oocytes from preovulatory follicles were retrieved from women selected for standard IVF treatment (Group A). Mature oocytes from antral follicles were recovered from women undergoing hCG-primed in vitro maturation (IVM) treatment (Group B). Patients groups were matched for age, BMI, FSH, AMH and antral follicle count (AFC) values. In vivo matured oocytes from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It is plausible that such a difference reflects an inherently different implantation ability between oocytes collected in IVM and ICSI cycles, for the reason that the former are retrieved from follicles of smaller size (6-12 mm). However, it may be interesting to note that in a recently published study, we observed comparable implantation rates between embryos developed from in vivo matured oocytes in IVM and ICSI cycles [30]. Assessment of embryo performance in vitro can provide at least a partial answer to the question of the competence of in vitro matured oocytes, being several embryo morphological parameters associated to developmental ability, even when measured at isolated time points [24].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is plausible that such a difference reflects an inherently different implantation ability between oocytes collected in IVM and ICSI cycles, for the reason that the former are retrieved from follicles of smaller size (6-12 mm). However, it may be interesting to note that in a recently published study, we observed comparable implantation rates between embryos developed from in vivo matured oocytes in IVM and ICSI cycles [30]. Assessment of embryo performance in vitro can provide at least a partial answer to the question of the competence of in vitro matured oocytes, being several embryo morphological parameters associated to developmental ability, even when measured at isolated time points [24].…”
Section: Discussionmentioning
confidence: 82%
“…However, the criteria of Bgood quality^adopted by these authors are rather disputable, including characteristics such as Bat least a 3-cell embryo on day 2 and a 6-cell embryo on day 3,^in contrast with an established consensus on embryo morphological evaluation [24]. In a recent study, we investigated the morphological quality and implantation potential of embryos developed from EC-MII in hCG-primed IVM cycles, but comparative data are presently lacking [30]. Introduction of time-lapse microscopy equipment among the options of the IVF laboratory has opened new horizons for the study of human preimplantation development in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary downregulation and ovarian stimulation were achieved with GnRH antagonist (Ganirelix, Merck Sharp & Dohme, Rome, Italy) and rFSH (Puregon, Merck Sharp & Dohme, Rome, Italy or Gonal-F, Merck, Rome, Italy) [38]. The initial dose and dose adjustments during treatment were chosen on a case-by-case basis according to patients' characteristics and response to gonadotrophins.…”
Section: Protocol For Ovarian Stimulationmentioning
confidence: 99%
“…Moreover, in the combined group (Group D, OTC + AIVM + OTIVM), most of the oocytes and mature oocytes obtained originated from the AIVM procedure. Importantly, the number of mature oocytes on the day of fertility preservation ("in-vivo matured oocytes") known to be with the highest chance of resulting in a pregnancy (Fadini et al, 2009(Fadini et al, , 2015Son and Tan, 2010), was higher in AIVM compared with OTIVM. Prior chemotherapy had no significant effect on the mean number of oocytes retrieved regardless of the retrieval method (AIVM or OTIVM) (data not shown).…”
Section: Patient Characteristicsmentioning
confidence: 99%